1997
DOI: 10.1159/000276954
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Measuring Distance on Laser-Doppler Measurements of the Micro-circulation in Human Nasal Mucosa

Abstract: Fourteen healthy volunteers were examined using rhinostereometry (RSM) and micromanipulator-guided laser-Doppler flowmetry (LDF) on the inferior turbinate and nasal septum. There were significant differences of the flowmetry readings at different distances from the mucosal surface within 0–1.0 mm. Changes in LDF values due to a change in distance between probe and mucosa seem to be an important artefact that will influence the flowmetry, especially if the probe is fixed to the framework of the nose (i.e. the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
8
0
2
Order By: Relevance
“…272 Use of the Doppler probe in the nose requires some important modifications, however, including a special probe, a stable support system and restraints in order to ensure that measurements assess the same microvascular field. 273 Because spontaneous fluctuations in NMBF or habituation-like decreases of 10-15% can occur, Druce (1984) has recommended that only NMBF changes in excess of 15% be considered reliable. 274 Although LDV holds considerable promise as an objective technique for measuring local irritant responses in the nose, most studies to date employing LDV have examined changes in NMBF following exposure to pharmacologic agents or histamines.…”
Section: Laser-doppler Velocimetrymentioning
confidence: 99%
“…272 Use of the Doppler probe in the nose requires some important modifications, however, including a special probe, a stable support system and restraints in order to ensure that measurements assess the same microvascular field. 273 Because spontaneous fluctuations in NMBF or habituation-like decreases of 10-15% can occur, Druce (1984) has recommended that only NMBF changes in excess of 15% be considered reliable. 274 Although LDV holds considerable promise as an objective technique for measuring local irritant responses in the nose, most studies to date employing LDV have examined changes in NMBF following exposure to pharmacologic agents or histamines.…”
Section: Laser-doppler Velocimetrymentioning
confidence: 99%
“…Using this technique we studied the impact of the distance between probe tip and mucosal surface [5]. We concluded that the LDF values were influenced by the measuring distance from the probe end to the mucosal surface.…”
Section: Introductionmentioning
confidence: 99%
“…We used a specially designed micromanipulator-guided probe for the flowmetry measurements. It was positioned approximately 0.3 millimeters from the medial surface of the inferior turbinate (16). A rhinostereometer equipped with the micromanipulator (Rhinomed, Sweden) was used to combine laser-Doppler flowmetry and rhinostereometry.…”
Section: Provocation Testmentioning
confidence: 99%